Reclamation and regeneration of boron in high-boron soils - F Peryea; F Bingham (California Agriculture, 1984)
Not available – first paragraph follows: Although boron is an essential plant nutrient, it becomes toxic to growing plants if excessive levels are present in the root zone. Soils containing high native concentrations of boron occur primarily in arid and semiarid environments where drainage or leaching, or both, are restricted. Soils periodically exposed to water containing appreciable amounts of boron, including groundwater and irrigation water, may also develop elevated levels of the element.